Building Disaster Resilience Through Social Protection Policies: A South African Perspective with Comparative Insights from SADC - Manga Mokofe, William (The Easta Journal Law and Human Rights, 2025)
South Africa is increasingly vulnerable to disaster-related risks arising from climate change, public health crises, and socio-economic instability. These threats disproportionately affect marginalised populations, exposing systemic weaknesses in governance and social protection systems. This article critically examines the evolving role of social protection in enhancing disaster resilience within the South African legal and policy framework, supplemented by comparative insights from selected Southern African Development Community (SADC) countries. It argues that current social protection mechanisms must be reconceptualised as proactive, risk-responsive systems. Drawing on legislation, case law, and policy innovations from South Africa, Zimbabwe, Malawi, and Zambia, the article proposes a shift toward transformative, inclusive, and anticipatory social protection that integrates disaster risk governance with developmental and constitutional mandates.